Nodding Syndrome (NS) in Northern Uganda - Kitara, David Lagoro; Mwaka, Amos Deogratius; Anywar, Denis Arony; Uwonda, Gilbert; Abwang, Bernard; Kigonya, Edward (British Journal of Medicine & Medical Research, 2013)
Aims: To conduct an epidemiological study to establish the association between malnutrition, metabolic disorder and Onchocerciasis to Nodding Syndrome (NS) in Northern Uganda. Study Design: Case-control study design. Place and Duration of Study: Odek and Atiak sub counties in Gulu and Amuru districts between 10th to 20th June 2012. Methodology: We recruited consecutively 101 children with probable NS in the 2 sub counties in Gulu and Amuru districts. Controls were from the same population but without symptoms of NS and were matched by age, sex and residents. History and physical examinations were conducted; anthropometry, blood samples and skin snips were obtained from cases and controls. Researchers were pediatricians, psychiatrists, nurses, laboratory scientists and epidemiologists. The research proposal was approved by the Ministry of Health and the IRB of Gulu University. Results: There was a statistically significant association between NS with malnutrition (t=0.142; p=0.044), Onchocerciasis (Χ2 = 152.74, p<0.001; OR 7.025 95% CI 3.891, 12.682) and High Anion Gap (Χ2=146.752, p<0.001; OR 6.313 95%CI 4.027, 9.895). Conclusion: Nodding syndrome is associated with metabolic disorder in young children who are malnourished and infected with Onchocerciasis.
: a Probable Metabolic Disorder